The LEGAL IMPLICATION of US-CHINA TRADE WAR ON INDONESIA’S POLICY RELATING TO PALM OIL INDUSTRY - Widayat, Wisnu; Hartati, Besse; Adillah, Muhammad Arief (Indonesian Law Journal, 2024)
Indonesia has been the largest producer and exporter of Crude Palm Oil (CPO) in the world since 2006.However, Indonesia faces complex challenges related to global CPO trade, starting from the global issue of China and the United States trade war, Including other strategic issues. The impact of the complexity of the US and China trade war is hitting Indonesia where palm oil from Indonesia is considered to be old and not environmentally friendly. This will impact market demand and disrupt the stability of national production. So an appropriate policy strategy is needed to manage this. The research objective is used as consideration for stakeholders in reviewing Indonesia's CPO policy in anticipation of the future. The research method uses a sociolegal approach. The research results show that the reasons for the decline in Indonesian CPO exports are the rejection of several European Union countries, which prevented the entry of Indonesian CPO and the influence of the China and United States trade war where soybean and sunflower oil are abundant as boycott between China and the US. Then, to fight against the European Union, Indonesia filed a lawsuit with the WTO, then certification of Palm Oil Plantations in Indonesia as part of the resistance will certainly have a positive impact on Indonesian CPO and developing biodiesel so that CPO consumption is used domestically.